(3efGQ GdCfhGQ aj CUhd Gdabgs - (3GdnqfnSaj, CHh GdHQcGJ, MGaX GdOjf, YHO Gddg Hf CMeO Hf eMehO, (B710 (3g`s ((3MSjf Hf CMeO (B( (3jGRLj RGOg (B)s)
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG Edi GdUQGW GdeSJbje hGdUdGI Ydi ef NJU HGdNdb GdYXje hYdi Bdg GdPjf bGehG HfUQI GdOjf Gdbhje s
(3BNQgG (B:s
(3cJfGhd eGd GdZjQ hdgPG EPG UHQ aj gPjf GdbSejf MJi bJd UGQ TgjOGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 67s
(3eYLe GdeDdajf (B2 / 228s
(3cTa GdXfhf (B2 / 1823s
(3gOjI GdYGQajf (B1 / 464s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs